(untitled) (Iranian Journal of Kidney Diseases, 2017)
Introduction. Nephrolithiasis is a common multifactorial kidney disease with worldwide distribution. Compelling evidence, regarding the function of kidney in maintaining the body homeostasis, suggests the role of oxidative stress in the pathogenesis of nephrolithiasis. Glutathione peroxidase 1 is a major antioxidant enzyme, preventing oxidative damage to renal cells by detoxifying hydrogen and lipid peroxides, which may involve in its pathogenesis. The purpose of the present study was to determine the possible association of glutathione peroxidase 1 gene (GPX1) proline-to-leucine substitution at amino acid 198 (Pro198Leu polymorphism) with the risk of developing nephrolithiasis in south Iranian patients. Materials and Methods. Association of Pro198Leu polymorphism in exon 2 of GPX1 gene was investigated in 150 patients with nephrolithiasis and 184 healthy age-, sex-, and ethnically-matched control group using polymerase chain reaction-restriction fragment length polymorphism. Results. Regression analysis demonstrated that the frequency of the genotypes carrying at least 1 Leu allele, in both dominant and codominant model for this allele, was significantly higher in patients compared with the controls. However, significant association was found neither with wild-type allele, nor with polymorphic allele with the risk of nephrolithiasis. Conclusions. Findings of our study provide potential support in favor of the role of oxidative stress in the pathogenesis of nephrolithiasis in patients from south of Iran. The results indicate that GPX1 may be a key player in nephrolithiasis development.